(untitled) (The Review of Diabetic Studies, 2023)
Type 1 diabetes (T1D) is a devastating disease precipitated by an autoimmune response directed at the insulinproducing beta-cells of the pancreas for which no cure exists. Stem cell-derived beta-cells show great promise for a cure as they have the potential to supply unlimited numbers of cells that could be derived from a patient’s own cells, thus eliminating the need for immunosuppression. Current in vitro protocols for the differentiation of stem cell-derived beta-cells can successfully generate pancreatic endoderm cells. In diabetic rodents, such cells can differentiate further along the beta-cell lineage until they are eventually capable of restoring normoglycemia. While these observations demonstrate that stem cell-derived pancreatic endoderm has the potential to differentiate into mature, glucose-responsive beta-cells, the signals that direct differentiation and maturation from pancreatic endoderm onwards remain poorly understood. In this review, we analyze the sequence of events that culminates in the formation of beta-cells during embryonic development, and we summarize how current protocols to generate beta-cells have sought to capitalize on this ontogenic template. We place particular emphasis on the current challenges and opportunities which occur in the later stages of beta-cell differentiation and maturation of transplantable stem cell-derived beta-cells. Another focus is on the question how the use of recently identified maturation markers such as urocortin 3 can be instrumental in guiding these efforts.